Asymmetric Price Effects of Competition - Saul Lach; Jose Luis Moraga-Gonzalez (Tinbergen Institute, 2009)
This paper examines how the distribution of prices changes with the number of competitors in the market. Using gasoline price data from the Netherlands we find that as competition increases, the distribution of prices spreads out: the low prices go down while the high prices go up, on average. As a result, competition has an asymmetric effect on prices. These findings, which are consistent with a theoretical model where consumers differ in the information they have about prices, imply that consumers' gains from competition depend on their shopping behavior. In our data, all consumers, irrespective of the number of prices they observe, benefit from an increase in the number of gas stations. The magnitude of the welfare gain, however, is greater for those consumers that are aware of more prices. We conclude that an increase in the number of gas stations has a positive but unequal effect on the welfare of consumers in the Netherlands.
Keywords: J1; 330; gasoline prices; imperfect information; number of firms and price distribution; Benzin; Preis; Unvollkommene Information; Preiswettbewerb; Tankstelle; Niederlande